Modelling of hydrodynamic processes inside coaxial channels of regular packing of cooling tower - Kuzmenko, Ihor; Gourjii, Alexandre (Видавництво Львівської політехніки, 2017)
The report is devoted to the analysis of physical processes associated with the motion of two-phase (fluid-gas) media inside the regular packing of cooling towers. Axisymmetric laminar flow inside the system of vertical coaxial infiniteness channels is considered. The mathematical formulation of the problem reduces to a boundary-value problem with the corresponding boundary conditions. The obtained analytical solution of the problem allowed carrying out a qualitative analysis of the flooding process in regular packing of cooling towers. It was shown that the flooding process begins on the inner surfaces of channels that located closer to the axis of the flow in regular packing of cooling tower.
Keywords: Two-phase flow; boundary-value problem; coaxial channels; flooding; regular packing; viscous flow